1997
DOI: 10.1002/ana.410410410
|View full text |Cite
|
Sign up to set email alerts
|

1H‐magnetic resonance spectroscopy—determined cerebral lactate and poor neurological outcomes in children with central nervous system disease

Abstract: By using proton magnetic resonance spectroscopy ((1)H-MRS), cerebral lactate has been shown to be elevated in a wide variety of pediatric and adult neurological diseases. In this study we compared 36 newborns, infants, and children with elevated lactate peaks on (1)H-MRS with 61 patients without an identifiable lactate signal. (1)H-MRS was acquired from the occipital gray and parietal white matter (8 cm3 volume, STEAM sequence with echo time = 20 msec, repetition time = 3.0 seconds) and data were expressed as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 49 publications
1
28
0
Order By: Relevance
“…In one study, elevated levels of brain lactate correlated significantly (P Ͻ .001) with serious long-term disability and death in a group of 36 pediatric patients with acute central nervous system injuries. 2 Mildly elevated concentrations of brain lactate were associated with reversible encephalopathy in a 14-year-old boy with Reye' s syndrome 35 and a patient with acute decompensation of maple syrup urine disease. 7 A proposed explanation for brain lactate production and brain death during FHF induced by D-galactosamine is outlined in Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In one study, elevated levels of brain lactate correlated significantly (P Ͻ .001) with serious long-term disability and death in a group of 36 pediatric patients with acute central nervous system injuries. 2 Mildly elevated concentrations of brain lactate were associated with reversible encephalopathy in a 14-year-old boy with Reye' s syndrome 35 and a patient with acute decompensation of maple syrup urine disease. 7 A proposed explanation for brain lactate production and brain death during FHF induced by D-galactosamine is outlined in Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Proton spectra of brain lactate at 1.5 T have been reported in a case of Reye' s syndrome 35 and in a variety of other diseases with neurological manifestations. [1][2][3][4][5][6][7] Unfortunately, unambiguous separation of the glutamine/flutamate complex (2.2-2.5 ppm) is not possible at 1.5 T. It was for this reason that the current study was performed at 9.4 T.…”
Section: Brain Lactate By Mrsmentioning
confidence: 99%
“…Because previous MRS studies in HII neonates have shown that reduced NAA/ Cr ratios correlate with impaired long-term developmental outcomes (13,16), future studies may find that MRS findings in hypothermia-treated neonates have a similar value in determining long-term neurological outcomes.…”
Section: Correlation Of Mri and Mrs Findings And Outcomementioning
confidence: 94%
“…A reference spectrum with eight acquisitions and no water suppression was acquired to use for eddy current correction. The OGM was chosen because it is located in a watershed cortical region and our previous studies show that this region is sensitive to global insults (13,22). Quantitative metabolite levels (in institutional units) and ratios were obtained for NAA (2.02 ppm), Cr (Cr + phosphocreatine; 3.0 ppm), Cho (3.2 ppm), myo-inositol (3.56 ppm), glutamate/glutamine (2.05 -2.5), and Lac (1.33 ppm) using LCmodel (35).…”
Section: Mri/mrsimentioning
confidence: 99%
See 1 more Smart Citation